THE CURRENT RISK ANALYSIS OF BORDER PORTS IN MONGOLIA - Gansukh Bat-Erdene; Urjin Odkhuu (International Journal of Innovative Technologies in Social Science, 2025)
Mongolia, a country with a low population density and an area of 1.56 million square kilometers, shares borders with Russia to the north and China to the south. Mongolia's border crossings play a crucial role in an economy heavily reliant on mining exports and constrained by limited land area.The fast-paced growth of the global economy, shifts in border management at the state border and border regions from foreign countries, the rise in operations and output of private businesses in border regions and zones domestically, the swift increase in the transportation of raw materials and products across state borders, and the movement of individuals, all have a direct impact on the country's economic performance. These factors have influenced Mongolia's economic security, which is fundamental to its existence, as well as border security, particularly border control activities carried out by organizations.Despite the Port Revitalization Policy's anticipated role in addressing the growing burden of border checkpoints and associated risks at ports, Mongolia's border checkpoints continue to operate with the same staffing levels and structure as in the 1980s and 1990s, resulting in unchanged throughput capacity. During that period, the number of passengers and vehicles crossing the Mongolian border was significantly lower, and the infrastructure and capacity were sufficient. However, the current workplace capacity is inadequate, leading to high workloads for border control agency employees. Additionally, there is no differentiation between vehicles entering and exiting customs, complicating the duties of border checkpoint employees and creating conditions for disorder.